How does a short-term hydrological disturbance changes the phytoplankton assemblages of a small lake? - Granado, Danielli Cristina [UNESP]; Perbiche-Neves, Gilmar; Henry, Raoul [UNESP] (Instituto de Ecologia y Ciencias Ambientales (IECA), 2022)
Hydrologic pulses in marginal environments are disturbances that produce extensive changes in the phytoplankton community. Our aim was to analyze the effects of a disturbance in the phytoplankton structure of a small and shallow lake (Cavalos Lake), a marginal lentic ecosystem isolated from the Paranapanema River (São Paulo, Brazil), located in the river-lake transition zone of a large power-plant reservoir. Overall, 27 samples were collected every three days for three months at the high-water period. The results evidenced the predominance of Aphanocapsa spp. Nägeli in the two first months. The Cyanobacteria species presented biomass predominance of 80% for more than four weeks, which characterized a phase of environmental equilibrium. This phase was interrupted by an abrupt increase in the hydrometric level, with the destabilization of the planktonic community and favoring of opportunistic species such as Cryptomonas brasiliensis A. Castro, C.E.M Bicudo & D. Bicudo 1992, which had a biomass predominance of 40% in two samplings. Next, there was an increase in the peak for Botryococcus braunii Kützing 1849, followed by an increase in diversity. The significant increase in the water volume in the second half of the period, through underground flow (Paranapanema River → Cavalos Lake), was a disturbance that promoted the high diversity values found in the lake after flooding.
Como um distúrbio hidrológico de curta duração pode causar modificação nas assembléias do fitoplâncton de um pequeno lago?
Keywords: Algae; algas; ambiente aquático marginal; disturbances; marginal aquatic environment; perturbações; succession; sucessão